Investigation of T cell receptors in the peripheral blood of patients with active pulmonary tuberculosis - Akbulut, H. H.; Deveci, F.; Celik, I.; Ilhan, F.; Turgut, T. (Wolters Kluwer Medknow Publications, 2009)
T cells have the capability of recognizing target cells through their T cell receptors (TCRs). Thus, the percentages of CD3 / gamma-delta () TCR and CD3 / alpha-beta () TCR T lymphocytes were investigated in active and inactive pulmonary tuberculosis (PT) patients and in healthy individuals. CD3 and CD3 / TCR cell percentages were significantly lower in all PT patients than in healthy subjects. Percentages of CD3 / and CD3/ TCR were not statistically different between active and inactive PT patients. It was concluded that TCR T cells might have a protective role in tuberculosis infection.
Keywords: Alpha; beta T cell; gamma; delta T cell; tuberculosis